Parents’ knowledge, attitudes and practices towards the prevention and treatment of dust mite allergy: a cross-sectional study in Shenyang (China) - Li Chen; Bing Dai; Si Liu; Lina Han; Qianlan Zhou; Qinzhen Zhang; Xiaowen Li; Wenxin Shen; Lishen Shan (BMJ Open)
Objective This cross-sectional study aimed to evaluate parents’ knowledge, attitudes and practices (KAP) concerning the prevention and treatment of dust mite allergy in children.Design This cross-sectional study survey was conducted from September to December 2022 at Shengjing Hospital, Affiliated with China Medical University.Participants A total of 503 parents of children with dust mite allergies participated, with 253 parents having children undergoing desensitisation treatment and 250 parents whose children did not. Selection criteria were carefully defined to include parents directly responsible for caring children with dust mite allergies.Primary and secondary outcome measures Two distinct questionnaires were administered to parents, tailored for those with and without children undergoing desensitisation treatment. These questionnaires covered demographic information, allergy diagnosis, treatment details and KAP related to dust mite allergy. Primary outcomes included parents’ scores on KAP regarding dust mite allergy prevention and treatment. Secondary outcomes involved analysing the interaction between these factors using pathway analysis.Results Parents of children undergoing desensitisation treatment exhibited higher scores for all items of knowledge, attitude and overall practice than those without desensitisation therapy (all p values<0.05). The pathway analyses revealed that in the non-desensitisation group, knowledge directly affected attitude (β=0.22, p<0.001) and attitude directly affected practice (β=0.16, p<0.001), but the knowledge did not affect practice (β=−0.01, 0.06, p<0.001). In the desensitisation group, knowledge directly affected attitude (β=0.13, p=0.028), but the practice was not affected by attitude (β=0.08, p<0.001) or knowledge (β=0.03, 0.12, p<0.001).Conclusions The study highlighted differing levels of KAP among parents of children with dust mite allergies. The KAP was influenced by desensitisation therapy status. While attitudes tended to be favourable, practices were suboptimal, particularly among parents whose children did not receive desensitisation treatment. These findings emphasise the importance of targeted educational interventions to enhance parental awareness and practices regarding dust mite allergy management, especially in cases where desensitisation treatment is not pursued. Further research is warranted to explore effective strategies for improving parental engagement and adherence to preventive measures.